1989
DOI: 10.1128/mcb.9.9.3829
|View full text |Cite
|
Sign up to set email alerts
|

Binding of heat shock proteins to the avian progesterone receptor.

Abstract: The protein composition of the avian progesterone receptor was analyzed by immune isolation of receptor complexes and gel electrophoresis of the isolated proteins. Nonactivated cytosol receptor was isolated in association with the 90-kilodalton (kDa) heat shock protein, hsp9O, as has been described previously. A 70-kDa protein was also observed and was shown by Western immunoblotting to react with an antibody specific to the 70-kDa heat shock protein. Thus, two progesterone receptor-associated proteins are ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
69
2
1

Year Published

1991
1991
2001
2001

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 191 publications
(78 citation statements)
references
References 73 publications
6
69
2
1
Order By: Relevance
“…There is evidence for persistent Hsp70 association with ligand bound receptors (48), although the functional significance of this interaction remains unknown. A new study on the Drosophila Ecdysone receptor, however, showed that Hsp90 and several other co-chaperones facilitate heterodimerization with RXR and DNA binding (49).…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence for persistent Hsp70 association with ligand bound receptors (48), although the functional significance of this interaction remains unknown. A new study on the Drosophila Ecdysone receptor, however, showed that Hsp90 and several other co-chaperones facilitate heterodimerization with RXR and DNA binding (49).…”
Section: Discussionmentioning
confidence: 99%
“…Although it is interesting to speculate that one of the major known heat shock proteins may serve the function of product X in our system, to date no direct evidence for this possibility has been found. However, there is evidence that HSPs can affect the DNA-binding properties of steroid receptors, since the glucocorticoid (49), progesterone (50,51), and estrogen receptors (52) have been shown to remain tightly complexed to HSP70 even after hormone-induced transformation of these receptors to the DNA-binding state. Moreover, purified HSP70 has been shown to enhance the in vitro DNA binding properties of the estrogen receptor (52).…”
Section: Discussionmentioning
confidence: 99%
“…For glucocorticoid receptors, hsp90 binding to receptor is required to maintain high-affinity ligand binding (3,26,40), but other steroid receptors that have been examined do not show this same dependency on hsp90. In all hsp90-nuclear receptor complexes, ligand-dependent activation of the receptor DNA-binding ability is accompanied by dissociation of hsp90 (14,17,31,43), and it appears likely that one hsp90 function is to repress DNA binding by receptor.Steroid receptor-hsp9O interactions provide a model for understanding hsp90 function, but exploiting this model has been hindered by the inability to reversibly assemble receptor-hsp90 complexes in vitro. This drawback was recently overcome by establishing certain physicochemical conditions that permit the use of rabbit reticulocyte lysate as a cell-free medium for assembly of hsp90 with chick progesterone receptor (PR) (44, 45) and rat glucocorticoid receptor (40).…”
mentioning
confidence: 99%
“…For glucocorticoid receptors, hsp90 binding to receptor is required to maintain high-affinity ligand binding (3,26,40), but other steroid receptors that have been examined do not show this same dependency on hsp90. In all hsp90-nuclear receptor complexes, ligand-dependent activation of the receptor DNA-binding ability is accompanied by dissociation of hsp90 (14,17,31,43), and it appears likely that one hsp90 function is to repress DNA binding by receptor.…”
mentioning
confidence: 99%